Princípio de extensão de Zadeh aplicado a funções não monótonas com dois parâmetros fuzzy - Melo, Gabriel Jesus Alves de (2008)
In the present work a computational method which permits the application of the extension principle to non-monotonic functions of two fuzzy parameters is presented. The extension principle is a basic concept of fuzzy set theory which allows the extension of a mathematical expression from the classical domain to the fuzzy domain. The harmonic oscillator with uncertain amplitude and frequency was chosen as a test case for the application and evaluation of the proposed method. The natural uncertainties which are present in a physical system were inserted into the classical model and by defuzzifcation of the center of gravity, a possible time evolution of the model was deduced. The results demonstrate that the fuzzy solution approximates the classical solution of the damped harmonic oscillator.